Faktor Yang Mempengaruhi Produktivitas Kerja Pada PT. Putra Nugraha Sentosa - Finsa Nuriya; Indah Wahyu Utami; Fery Wisnu Saputro (Jurnal Rekayasa Proses dan Industri Terapan, 2024)
Productivity is one component that must be owned by a company to achieve the goals that have been set. One of the reasons companies find it difficult to achieve their goals is low employee productivity. Therefore it is necessary to make an effort to increase employee productivity because productivity can describe the level of efficiency of employees at work. So this study aims to determine what factors influence work productivity at PT. Putra Nugraha Sentosa and how to increase work productivity. This type of research is quantitative because it uses data that requires calculation and uses qualitative analysis to describe the data that has been obtained so that the data will be clearer. To analyze the author's data using validity test, reliability test, multiple linear regression analysis and partial test (T test) assisted by using the SPSS program. The results of this study obtained that all items in the study could be declared valid and the 5 variables in the study could be declared reliable. Multiple linear regression test obtained the equation Y = 29.252 + 0.302X1 + 0.318X2 + 0.446X3 + 0.467X4 + e. Then from the results of the partial test (T test) it is known that the variables of work discipline, work motivation and work environment have a significant effect on work productivity.